Generous orthodoxies: essays on the history and future of ecumenical theology - Peterson, Paul Silas (Pickwick Publications, 2020)
Part I.Ecumenical Reform Theologies : --1.Yves Congar : the birth of "Catholic ecumenism" /Andrew Meszaros --2.Edmund Schlink : ecumenical theology /Matthew L. Becker --3.Otto Hermann Pesch : ecumenical scholasticism /Dorothea Sattler --4.George Lindbeck : ecumenical unity through ecclesial particularity /Ronald T. Michener --5.John D. Zizioulas : a pioneer of ecumenical dialogue and Christian unity /Nikolaos Asproulis --Part II.Overcoming Liberal-Conservative Polarities : --6. Hans Frei : beyond liberal and conservative /Ben Fulford --7.Wolfhard Pannenberg : liberal orthodoxy /Friederike Nüssel --8.Stanley J. Grenz : the evangelical turn to postliberal theological method /Jay T. Smith --Part III.Boundary Crossings in Philosophical, Systematic, and Ethical Theology : --9.David Tracy : difference, unity, and the analogical imagination /William E. Myatt --10.Robert W. Jenson : God's way and the ways of the church /Christophe Chalamet --11.Stanley Hauerwas : witnessing communities of character /Victoria Lorrimar --12.Marilyn McCord Adams : philosophy, theology, and prayer /Christine M. Helmer --Part IV.Ecumenical Theology Today : --13.Pentecostalism and Christian orthodoxy : revision, revival, and renewal /Wolfgang Vonday --14.Shifting paradigms : future ecumenical challenges /Johanna Rahner --15.Theology today in India : ecumenical or interreligious? /Michael Amaladoss --16.Next steps, and visions? Lutheran perspectives on doctrinal ecumenism /Bernd Oberdorfer